Intraocular Pressure Dynamics and Ischaemic Risks During Air Travel Post-Gas Tamponade: A Systematic Review and Meta-Analysis - Vina Yuwanda; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita; I Made Ady Wirawan (HM Publisher, 2026)
Background: Gas tamponade is a widely used surgical intervention for retinal detachment repair. However, intraocular gas bubbles expand at altitude owing to Boyle's law, potentially causing severe intraocular pressure (IOP) elevation and ischaemic complications. The safety of air travel for patients with residual intraocular gas remains insufficiently characterised. Methods: We conducted a systematic review and meta-analysis of empirical and computational studies examining IOP dynamics during simulated or actual altitude exposure in eyes with intraocular gas. We searched MEDLINE, Embase, Web of Science, Scopus and PubMed Central through March 2024 for peer-reviewed publications without language restrictions. Study selection followed PRISMA 2020 guidelines with predefined eligibility criteria. Data were extracted in duplicate, and risk of bias assessed using the Newcastle-Ottawa Scale. Random-effects meta-analysis calculated standardised mean differences (SMD) with 95% confidence intervals (CI). Sensitivity analyses stratified findings by study type. Results: The primary analysis included three empirical studies (n = 47 eyes) showing IOP increase of SMD = 3.03 (95% CI: 2.18–3.89; I² = 17.16%, τ² = 0.11). Sensitivity analysis including all four studies (one computational model) yielded SMD = 4.67 (95% CI: 1.52–7.82; I² = 95.67%, τ² = 9.81). Individual study estimates ranged from SMD = 2.52 (Mills 2001) to SMD = 8.65 (Gsellman 2016, computational). Risk of bias was generally low to moderate. No significant publication bias was detected. Conclusion: Patients with residual intraocular gas who undertake air travel face meaningful IOP elevation at altitude. The risk of anterior segment ischaemic complications warrants careful patient counselling, altitude restriction recommendations, and prophylactic pharmacotherapy. Future prospective studies should evaluate optimal clinical protocols.